Data privacy in cloud computing: A comparative study of privacy preserving techniques - Kambala , Gireesh (International Journal of Scientific Research and Management (IJSRM), 2025)
Cloud computing has emerged as a key service delivery model for business data storage and processing during the digital evolution. Nevertheless, the growth in cloud adoption has also brought great concern in matters concerning data security. This work proposes an in-depth comparison of all privacy preservation techniques in cloud computing including Cryptography, Anonymization, Access Control, Secure Multiparty Computation, and Blockchain. These techniques are assessed on the grounds of performance, scalability, complexity of implementation and effectiveness in the protection of the sensitive data. The research not only can find out more about these techniques, but also can also realize practical difficulties and achievements when applying these techniques. Based on case study and applications, the technique is also evaluated with its more practical concerns. Moreover, the study discusses potential threats, which were discovered and contemplated during the course of conducting the research, and finds out voids in the current knowledge stream, and provides guidelines for future work. Through integrating theoretical knowledge with best practices, this work intends to present a solid foundation to mitigate data privacy in cloud computing with secure and dependable cloud environments.